Biallelic mutations in FDXR cause neurodegeneration associated with inflammation. Issue 12 (December 2018) - Slone, Jesse; Peng, Yanyan; Chamberlin, Adam; Harris, Belinda; Kaylor, Julie; McDonald, Marie; Lemmon, Monica; El-Dairi, Mays; Tchapyjnikov, Dmitry; Gonzalez-Krellwitz, Laura; Sellars, Elizabeth; McConkie-Rosell, Allyn; et al.
Abstract Mitochondrial dysfunction lies behind many neurodegenerative disorders, owing largely to the intense energy requirements of most neurons. Such mitochondrial dysfunction may work through a variety of mechanisms, from direct disruption of the electron transport chain to abnormal mitochondrial biogenesis. Recently, we have identified biallelic mutations in the mitochondrial flavoprotein "ferredoxin reductase" (FDXR) gene as a novel cause of mitochondriopathy, peripheral neuropathy, and optic atrophy. In this report, we expand upon those results by describing two new cases of disease-causingFDXR variants in patients with variable severity of phenotypes, including evidence of an inflammatory response in brain autopsy. To investigate the underlying pathogenesis, we examined neurodegeneration in a mouse model. We found thatFdxr mutant mouse brain tissues share pathological changes similar to those seen in patient autopsy material, including increased astrocytes. Furthermore, we show that these abnormalities are associated with increased levels of markers for both neurodegeneration and gliosis, with the latter implying inflammation as a major factor in the pathology ofFdxr mutations. These data provide further insight into the pathogenic mechanism of FDXR-mediated central neuropathy, and suggest an avenue for mechanistic studies that will ultimately inform treatment.